Penguatan Kepemimpinan Kepala Sekolah Dalam Manajemen Sekolah Ramah Anak Sebagai Aktivis Perlindungan Anak Di Kutai Timur - Mulawarman, Widyatmike Gede; Nurlaili, Nurlaili; Halimah, Siti; Basuni, Basuni; Yuliani, Rini Dwi (Literasi Nusantara Publisher, 2024)
This community service activity aims to enhance the quality of school principal leadership in the context of child-friendly school management. The main targets of this activity are principals of various primary and secondary schools in the East Kutai region. The methods used in this activity include workshops, training, consultations, and the development of training materials. The main challenges faced by principals and teachers in realizing child-friendly schools are the lack of facilities and infrastructure that support child-friendly schools and insufficient understanding of what constitutes a child-friendly school. Principals and teachers need a comprehensive understanding of child-friendly schools. Guidance from the PKM Team provides significant contributions in delivering information, strategies, and approaches that support principals in training their staff and teachers about child-friendly management practices. Additionally, through this PKM, there has been an increase in collaboration between schools, parents, and other related parties in efforts to protect children in the school environment. This community service activity has made a significant contribution to creating a safer, more inclusive school environment that supports child development and strengthens the role of principals as child protection agents in the school environment.